PARP Inhibitors in Prostate and Urothelial Cancers - Garje, Rohan; Vaddepally, Raju Kumar; Zakharia, Yousef (Frontiers in Oncology, 2020)
Poly(ADP-ribose) polymerase (PARP) inhibitors targeting DNA repair gene mutations have shown significant clinical benefit in patients with ovarian and breast cancers. In metastatic prostate cancers, the prevalence of DNA repair gene mutations is up to 20%, and early phase studies have shown clinical activity of PARP inhibitors. Numerous clinical trials with either PARP monotherapy or in combination with other therapeutic agents are ongoing in prostate cancer. In this comprehensive review, we provide the rationale, efficacy, and safety data of PARP inhibitors in prostate as well as urothelial cancers.